2010
DOI: 10.2746/042516409x478479
|View full text |Cite
|
Sign up to set email alerts
|

Associations between physiotherapy findings and subsequent diagnosis of pelvic or hindlimb fracture in racing Thoroughbreds

Abstract: Earlier detection of (impending) pelvic or hindlimb fracture in racing Thoroughbreds could reduce the incidence of catastrophic fractures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 28 publications
0
8
0
Order By: Relevance
“…Although body condition scoring is frequently used as a guide for nutritional advice [13][14][15], there is no comparable scale for evaluation of muscle development which could potentially be useful in relation to training, nutrition, and detection of orthopedic problems, such as pelvic or hindlimb fracture [16]. Alterations in muscle development may be related to back pain [17,18], lameness [19], conformation [20], rider [21,22], saddle fit [23], and exercise history [24].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although body condition scoring is frequently used as a guide for nutritional advice [13][14][15], there is no comparable scale for evaluation of muscle development which could potentially be useful in relation to training, nutrition, and detection of orthopedic problems, such as pelvic or hindlimb fracture [16]. Alterations in muscle development may be related to back pain [17,18], lameness [19], conformation [20], rider [21,22], saddle fit [23], and exercise history [24].…”
Section: Introductionmentioning
confidence: 99%
“…Alterations in muscle development may be related to back pain [17,18], lameness [19], conformation [20], rider [21,22], saddle fit [23], and exercise history [24]. Visual and palpation assessment of the posture (1) rostral aspect of the facial crest, (2) wing of atlas, (3) proximal aspect of the scapular spine, (4) over the cranial eminence of the greater tubercle of the humerus, (5) the lateral epicondyle of the humerus over the lateral collateral ligament of the elbow, (6) lateral styloid process of the radius, (7) proximal aspect of the third metacarpal bone at the junction with the base of the fourth metacarpal bone, (8) distal aspect of the third metacarpal bone over the lateral collateral ligament of the metacarpophalangeal joint, (9) lateral collateral ligament of the distal interphalangeal joint (designated coronary band), (10) dorsal aspect of the hoof wall at the level of the coronary band, (11) dorsal aspect of the hoof wall at the level of the coronary band, (12) lateral collateral ligament of the distal interphalangeal joint (designated coronary band), (13) distal aspect of the third metatarsal bone over the collateral ligament of the metatarsophalangeal joint, (14) proximal aspect of the third metatarsal bone at the junction with the base of the fourth metatarsal bone, (15) midtalus, (16) proximal aspect of fibula, (17) medial epicondyle of the distal femur, (18) proximal aspect of the greater trochanter of the femur, (19) ischiatic tuberosity, (20) top of tail, (21) proximal aspect of the tuber coxae, (22) tuber sacrale, (23) spinous process of the fourth lumbar vertebra, and (24) spinous process of the sixth thoracic vertebra. Table 1): (1) cervical, (2) thoracic, (3) lumbosacral, (4) pelvic, (5) hindlimb, and (6) abdominal.…”
Section: Introductionmentioning
confidence: 99%
“…There is an increasing view that a reductionist approach to lameness should not be taken, but that of an integrative approach, not just looking at the pathophysiology, but also the associated adaptive changes and causative factors (Loomans et al 2009;Paulekas and Haussler 2009). A recent case-control study indicated that physiotherapy could be used to detect, and recognise signs of, impending fractures in racing Thoroughbreds (Hesse and Verheyen 2010).…”
Section: Discussionmentioning
confidence: 98%
“…The considerable number of injuries in racing horses encourages intensive physiotherapeutic treatment, of which massage is the main type (Haussler, 2009;Scott and Swenson, 2009). However, Hesse and Verheyen (2010) found that it is worth preparing horses for such therapy. Both the behavioural assessment and the cardiac parameters measured during the massage sessions indicate that the period during which horses become accustomed to this therapy should last about two months.…”
Section: Discussionmentioning
confidence: 99%